Framework for sustainable development education and lessons learned - Santosh Kumar Mishra (African Journal of Environmental Economics and Management, 2013)
Today, educators face a compelling responsibility to serve society by fostering the transformations needed to set the path to sustainable development. The time has come to ensure that the concepts of education for sustainability - IN THE BROADEST SENSE - are discussed and woven into a framework upon which current and future educational policy is based. Understanding the principles of sustainability and the interdependence of the environment, the economy, and social systems can help learn to make the changes necessary to become effective stewards of natural resources and the environment. Education for sustainability of which many other disciplines are indispensable components, will engage partners from all arenas - adult education, on-the-job training, other formal and non-formal education programs, and the media - to reach out to as many individuals as possible. Clearly, the time is right to engage in a dynamic process to educate not only children but all citizens about the economic and environmental realities of today’s world. Individuals from business and government, the educational community, and non-governmental organizations (NGOs) need to come together to share common themes, ideas, and challenges related to education for sustainability. This paper aims to give an insight into the framework within which skills and education can be imparted for environment and sustainability. It also: (a) Looks into the significant lessons learnt in implementation of education for sustainable development programmes; and (b) Discuses role of students in sustainable development initiatives. The paper concludes that achieving a sustainable future will not happen unless the educational system imparts education for sustainable development to citizens and specialists who understand the interconnections among the environmental, economic and social disciplines.